2012
DOI: 10.1007/s12094-012-0898-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of an isogenic cell line with a radioresistant phenotype

Abstract: In this model, the emergence of radiation resistance was associated with the acquisition of biological traits that support more aggressive behaviour of cancer cells. We have generated a model that will be useful for mechanistic studies and development of rational treatments against radiation resistance in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
4
17
0
Order By: Relevance
“…The DNA damage response pathway triggers gene transcription to repair the damage, and unrepaired DNA damage leads to apoptosis. Many previous reports have demonstrated an increase in the capacity to repair DSBs, the main type of DNA damage induced by ionizing radiation [29, 30], as well as reduced apoptosis in radiation-resistant sublines compared with the radiosensitive parent line [31, 32]. Because Hh signaling regulates many genes involved in DNA repair processes, targeting Hh signaling has the potential to increase sensitivity to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA damage response pathway triggers gene transcription to repair the damage, and unrepaired DNA damage leads to apoptosis. Many previous reports have demonstrated an increase in the capacity to repair DSBs, the main type of DNA damage induced by ionizing radiation [29, 30], as well as reduced apoptosis in radiation-resistant sublines compared with the radiosensitive parent line [31, 32]. Because Hh signaling regulates many genes involved in DNA repair processes, targeting Hh signaling has the potential to increase sensitivity to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest that radioresistance is associated with the enhanced repair of radiation-induced DNA damage [1] [7] [18] [19]. Our previous study also showed that X-ray-induced phosphorylated histone H2AX (γH2AX) foci disappear more rapidly in HepG2-8960-R than in parental HepG2 [1].…”
Section: Introductionmentioning
confidence: 82%
“…The molecular basis of radioresistance remains to be elucidated. The radioresistant phenotype has been correlated with characteristics such as the enhanced repair of IR-induced DNA damage [1] [2] [3] [4], overexpression of cyclin D1 [5] [6], higher rates of cell growth and migration [7], a lower concentration of reactive oxygen species (ROS) in cells [8] [9] [10], inactivation of apoptotic proteins [11] and alterations in radiation-induced autophagy [12] [13]. A disadvantage of studying radioresistance is the lack of adequate radioresistant models reflecting the clinical features of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simvastatin was dissolved in DMSO for cell culture experiments and used at doses ranging from 1 to 25 μM depending on the type of experiment, while it was dissolved in 1,2-propanediol in distilled water 1:1 (vol/vol) for animal treatments and used at a fixed dose of 50 mg/kg per day (simvastatin, DMSO, and propanediol were purchased from Sigma-Aldrich, St Louis, MO). Drug doses were based on preliminary studies from our group and previously published works [10] , [11] , [12] , [13] , [14] , [15] . We have varied doses and timings to adapt them to the type of assay to examine the effect of concomitancy between drugs for at least a period of 48 hours.…”
Section: Methodsmentioning
confidence: 99%